The Safety of Deposits in EU Banks in View of Cyprus’s Bailout Tax - Kondej, Mikołaj (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the right to property in the context of the safety of bank deposits in the European Union. In order to present that topic the author focus on the example Cyprus’s bailout tax concluding that it should be stated that deposits in banks are never completely safe.